De-regulation of gene expression and alternative splicing affects distinct cellular pathways in the aging hippocampus - Stilling, Roman M.; Benito, Eva; Gertig, Michael; Barth, Jonas; Capece, Vincenzo; Burkhardt, Susanne; Bonn, Stefan; Fischer, Andre (Frontiers in Cellular Neuroscience, 2014)
Aging is accompanied by gradually increasing impairment of cognitive abilities and constitutes the main risk factor of neurodegenerative conditions like Alzheimer’s disease. The underlying mechanisms are however not well understood. Here we analyze the hippocampal transcriptome of young adult mice and two groups of mice at advanced age using RNA sequencing. This approach enabled us to test differential expression of coding and non-coding transcripts, as well as differential splicing and RNA editing. We report a specific age-associated gene expression signature that is associated with major genetic risk factors for late-onset Alzheimer’s disease. This signature is dominated by neuroinflammatory processes, specifically activation of the complement system at the level of increased gene expression, while de-regulation of neuronal plasticity appears to be mediated by compromised RNA splicing.